2015
DOI: 10.1002/cssc.201501093
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Epimerization of Aldoses Using Layered Niobium Molybdates

Abstract: Both non-acidic LiNbMoO6 and strongly acidic HNbMoO6 efficiently catalyze the epimerization of sugars including glucose, mannose, xylose, and arabinose in water. The reactions over these oxides reached almost equilibrium within a few hours where yields of corresponding epimers from glucose, xylose, and arabinose were 24-29%. The layered mixed oxides functioned as heterogeneous catalysts and could be reused without loss of activity, whereas bulk molybdenum oxide MoO3 was completely dissolved during the reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
47
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(52 citation statements)
references
References 42 publications
4
47
0
Order By: Relevance
“…For instance non-acidic LiNbMoO 6 and strongly acidic HNbMoO 6 efficiently catalyze epimerization of glucose to mannose without any isomer formation. 20 In contrast, glucose isomerization into fructose via an intramolecular 1,2-hydride shift mechanism with Lewis acid catalysts such as Sn-β zeolites can be very efficient giving a 55% glucose conversion and a 32% yield of fructose in water at 110°C. 21 Besides fructose, an epimer -mannose -was also formed.…”
mentioning
confidence: 99%
“…For instance non-acidic LiNbMoO 6 and strongly acidic HNbMoO 6 efficiently catalyze epimerization of glucose to mannose without any isomer formation. 20 In contrast, glucose isomerization into fructose via an intramolecular 1,2-hydride shift mechanism with Lewis acid catalysts such as Sn-β zeolites can be very efficient giving a 55% glucose conversion and a 32% yield of fructose in water at 110°C. 21 Besides fructose, an epimer -mannose -was also formed.…”
mentioning
confidence: 99%
“…The total sugar yields increased with milling time ( Figure 6). [50] The product distributions werem aintained from the beginning of ball milling,w hereas the total yields increased monotonically.T his suggests that short-chain oligomers were not depolymerized into smaller molecules. Mannose was formed because of the selective epimerizationo fg lucose over HNbMoO 6 ,a sw e recently reported.…”
Section: Characterization Of Mixed Powdersa Fter Ball Millingmentioning
confidence: 99%
“…Mannose was formed because of the selective epimerizationo fg lucose over HNbMoO 6 ,a sw e recently reported. [50] The product distributions werem aintained from the beginning of ball milling,w hereas the total yields increased monotonically.T his suggests that short-chain oligomers were not depolymerized into smaller molecules. In other words, most of the resultant water-soluble sugars were not produced by successive degradation of oligosaccharides but by random andd irect decomposition of cellulose.…”
Section: Mechanochemical Depolymerization Of Cellulose In the Presencmentioning
confidence: 99%
“…have demonstrated that Mo‐based polyoxometalates are stabilized by electrostatic interaction with heteroatoms . Niobium‐modified layered LiNbMoO 6 and HNbMoO 6 have been shown to be stable in the epimerization of glucose without the leaching of Mo species . Although molybdenum‐based polyoxometalates with Keggin structure can epimerize glucose to mannose efficiently, the synthetic processes of Mo‐based polyoxometalates are complex.…”
Section: Introductionmentioning
confidence: 99%